THE ROLE OF SOCIAL MEDIA MARKETING IN THE SALE OF FROZEN FOODS - Abdurashid Yakubov; Maftuna Sayfullaeva; Dono Kadirbergenova; Nozima Azimjonova (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
This work aims at identifying the effect of SMM on frozen food sales in Uzbekistan with special reference to Instagram, Facebook, and TikTok. Growing market for frozen foods has made the global market reach USD 232.40 billion in 2020 and it is expected to reach USD 389.90 billion in the year 2030 and due to urging need of enhancing brand awareness, customer engagement, and brand loyalty, the brands are using social media platform actively. Thus, the study adopts a quantitative research method to validate the research hypotheses and questionnaire that was completed by 106 consumers in Tashkent, Uzbekistan, were used to assess the link between SMM activities and frozen food sales. Consequently, the research results show that social media marketing, while having a positive effect on brand trust and customer participation, has a rather limited effect on the direct purchases and market share. They find that the branded frozen food has more market share when compared to unbranded frozen foods, and that the consumers’ trust plays the role of a mediator. Nevertheless, pointing to the positive effects of SMM, the research identifies a lack of content satisfaction and consumer interaction – it is, thus, argued that frozen food brands should enhance the focus on their digital marketing approaches to target younger consumers more effectively. Finally, this research finds that there is a strong potential to leverage social media marketing for the frozen food industry especially within Uzbekistan and other growing economy attracting a rising trend in digital food retail.